2021
DOI: 10.1089/heq.2021.0017
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Minority Pregnant Patients with Low-Income Experiences of Perinatal Care: A Scoping Review

Abstract: Purpose: The maternal mortality ratio for the United States (US) has consistently risen over recent decades. This mortality is especially pronounced within minority populations who experience a maternal mortality and morbidity rate that are much higher than their non-Hispanic white counterparts. Qualitative data are critical in gaining true insight from minority pregnant and postpartum persons. Such data should serve as the basis for building interventions and programs that seek to eradicate perinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
(311 reference statements)
3
11
0
Order By: Relevance
“…The findings from scoping review of low-income, underserved patients’ experiences with perinatal care by Wishart et al 12 are consistent with the results arrived at with this current review. Specifically, there are commonalities between Wishart’s themes of Communication, Connection, and Support and our themes of Ineffective Communication, Disrespect, and Lack of Established Relationship.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The findings from scoping review of low-income, underserved patients’ experiences with perinatal care by Wishart et al 12 are consistent with the results arrived at with this current review. Specifically, there are commonalities between Wishart’s themes of Communication, Connection, and Support and our themes of Ineffective Communication, Disrespect, and Lack of Established Relationship.…”
Section: Discussionsupporting
confidence: 89%
“…In a recent scoping review, Wishart et al 12 examined perinatal care experiences for low-income, underserved pregnant women. The authors concluded that support, education, connection, communication, and trust were vital to perinatal care.…”
Section: Perinatal Health Disparities and The Patient-clinician Relat...mentioning
confidence: 99%
See 1 more Smart Citation
“…The USA has the highest maternal mortality rate of developed countries, where African American women are 2–3 times likely to die and experience morbidities during pregnancy compared with Caucasian women 4. Publicly insured, low-income women especially need prenatal care that mitigate health and racial disparities 5. In 2013, there were 289 000 maternal deaths, of which 60% occurred in sub-Saharan Africa and 24% in Asia 6.…”
Section: Commentarymentioning
confidence: 99%
“…Yet, despite this, the landscape of interventions that are in development or testing to target improvements in patient-provider relationships for Black pregnant people is largely unknown. Previous work has synthesized the types of communication and interaction that Black pregnant people perceive as biased or stigmatizing (Wishart et al, 2021), but a review of interventions to mitigate the harmful effects of poor patient-provider relationships or change the way patients and providers interact does not exist.…”
Section: Introductionmentioning
confidence: 99%